Effect of Organic and Inorganic Sources of Nitrogen of on Growth, Yield and Economics of Baby Corn (Zea mays L.) - Rani, P. Leela; Rao, A. Ramachandra; Balaswamy, K.; Ahmed, S. Riazidduin (International Journal of Bio-resource and Stress Management, 2011)
The results of field experiment conducted at Agricultural Research Institute, ANGRAU, Rajendranagar, Hyderabad during rainy (kharif) season of 2005 and 2006 revealed that recommended dose of N (RDN) through fertilizer application (90 kg N ha-1) recorded significantly higher number of cobs plant-1, cobs ha-1, baby corn green ear yield, stover yield and nutrient uptake over combined application of 75% N through fertilizer + 25% N through Neem cake, 50% of N through fertilizer + 50% of N through Neem cake. However, the number of days taken to first harvest and harvest duration (First harvest to final harvest) were not influenced by N management practices. Higher net returns (` 30767 ha-1) and B:C ratio (2.3) were obtained with recommended dose of N application. Out of all the cultivars tested VL-78 recorded significantly higher baby corns plant-1 (2.92), more green ear weight (23.3 g), harvest duration (25.2 days), baby corn yield (5511 kg ha-1), N and K uptake, also net returns (`36693 ha-1) and B:C ratio (2.5). Significantly higher net returns were obtained by cultivar VL-78 with combined application of 75% N through fertilizer + 25% N through Neem cake.